1968
DOI: 10.1098/rspa.1968.0169
|View full text |Cite
|
Sign up to set email alerts
|

Propyl radical isomerization and heterogeneous effects in the pyrolysis of propane below 500°C

Abstract: A detailed study of product formation in the initial stages of pyrolysis of propane has been carried out with a static system at pressures between 26 and 416 mmHg at temperatures between 441 and 503°C. Under all conditions employed the stoicheiometry of the reaction may be represented as (1 + α ) C 3 H 8 = H 2 + C 3 H 6 + α (CH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…They are in agreement with an initial order of product formation n o near 1.2 (cf Table I). This result agrees with those of Leathard and Purnell [9,10], Jézéquel et al [14 -17], and Juste et al [26,27]. Concerning the temperature effect, the activation energy E o is near 69 kcal mol Ϫ1 for the formation of each of the main primary products (see Table I).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…They are in agreement with an initial order of product formation n o near 1.2 (cf Table I). This result agrees with those of Leathard and Purnell [9,10], Jézéquel et al [14 -17], and Juste et al [26,27]. Concerning the temperature effect, the activation energy E o is near 69 kcal mol Ϫ1 for the formation of each of the main primary products (see Table I).…”
Section: Resultssupporting
confidence: 93%
“…Two main stoichiometries: extrapolated at zero time, remains in the range 1.4 -1.6 and slightly decreases as initial pressure of propane or temperature increases. The observed effects are similar to those previously described by Leathard and Purnell [9,10]. Figures 2 and 3 show the respective influences of propane initial pressure and of temperature on the concentration-time profiles of methane in an unpacked reactor (s/v ϭ 0.8 cm Ϫ1 ).…”
Section: Resultssupporting
confidence: 79%
“…Equation [11] indicates that when reactions [lo] or [ I l l predominate, the overall order is 0.5. When reaction [8] predominates, the overall order is 1.5, and when reaction [9] predominates it is between 0.5 and 1.5 (approximately 1.35 (3)).…”
Section: Overall Reaction Ordermentioning
confidence: 99%
“…In the previous recent publication already mentioned (3), an equation was developed to predict the reaction order for the pyrolysis of n-butane C;It2 C;It2(Ffn + Fn)(rmrf1)112 k6[C4H1oIe O < e < l a n d O < u < 1 It was also shown that equations such as [11] for the overall order may be expressed in terms of the kinetic parameters of the propagation reactions; in this case, they are the parameters listed in Table I, and eq. [I] represents the product distribution3.…”
Section: Overall Reaction Ordermentioning
confidence: 99%
See 1 more Smart Citation